Screening the physicochemical properties of thermosonically treated pomelo juice - Wan Marzuki Rashidi, Wan Nur Ain Syukriah; Abdullah, Norazlin; Muhammad, Norhayati; Othman, Siti Amira; Sze, Hui Jong (UTHM, 2018)
Pomelo (Citrus grandis L. Osbeck) tastes sweet, slightly acidic with a hint of bitterness. It has many beneficial health effects. The aim of this study was to evaluate the effect of thermosonication treatment on physicochemical properties of pomelo juice by subjecting the juice to different times and temperatures. Thermosonication is a treatment where ultrasound is conducted at moderate temperature ranging between 37 and 75°C. Pomelo juice was treated with thermosonication for 2, 46 and 90 minutes with initial temperature ranging from 20C, 35C and 50C. The treated juice were analysed for its physicochemical properties, such as colour values (L*, a* and b*), total soluble solids (TSS) content, pH, titratable acidity and electrical conductivity. Results showed that the lightness (L*), pH, titratable acidity and electrical conductivity of the pomelo juice does not changed during treatment. However, redness (a*) and yellowness (b*) and TSS showed highest reading at 50C at 90 minutes.